Interpellations around the reconstruction of memories in gender keys (Papeles, 2023)
This article recovers the findings obtained in the framework of the investigations that we have been carrying out in the field of collective memories and the processes of struggles and disputes for places of memory and commemorations in territories - neighborhoods of the city of Córdoba. From there, various lines of inquiry emerge that account for the complexity and particularity that these processes acquire in each spatial locus; In this work we try to give an account of the gendered memories and the place that women occupy in these daily and collective frameworks that place them as protagonists of a silenced and forgotten history, but that acquire visibility in a present that recovers and reconstructs them.
Keywords: History; memory; gender; territories; places of memory